The Value and Role of Contemplative Practices for Effective Teaching and Transformative Learning in Adult and Higher Education - Qi Sun (Adult Education Research Conference, 2007)
This paper presents and discusses value and role of contemplative practices for effective teaching and transformative learning in adult and higher education.